2022
DOI: 10.3389/fendo.2021.682145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translational Potentials of Stem Cell-Derived Extracellular Vesicles in Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is an organ-specific disease characterized by the deficiency of insulin caused by the autoimmune destruction of pancreatic islet β cells. Stem cell-based therapies play essential roles in immunomodulation and tissue regeneration, both of which hold great promise for treating many autoimmune dysfunctions. However, their clinical translational potential has been limited by ethical issues and cell transplant rejections. Exosomes are small extracellular vesicles (EVs) released by almost all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 178 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…EVs are nanosized particles secreted by cells, which contain a variety of biologically active substances, such as lipids, proteins, and RNAs, and play an important role in intercellular communication, cell survival and apoptosis, and the regulation of disease progression. Interestingly, numerous previous studies have shown that SC-EVs, especially exosomes, have repairing effects similar to SCs without the risk of tumor formation and can be stably preserved for transport, which has attracted a great deal of attention from researchers ( 2 , 17 ). To explore the process and trend of SC-EVs for DM, this study conducted a bibliometric analysis of the publication on SC-EVs for DM from 2017 to 2021.…”
Section: Discussionmentioning
confidence: 99%
“…EVs are nanosized particles secreted by cells, which contain a variety of biologically active substances, such as lipids, proteins, and RNAs, and play an important role in intercellular communication, cell survival and apoptosis, and the regulation of disease progression. Interestingly, numerous previous studies have shown that SC-EVs, especially exosomes, have repairing effects similar to SCs without the risk of tumor formation and can be stably preserved for transport, which has attracted a great deal of attention from researchers ( 2 , 17 ). To explore the process and trend of SC-EVs for DM, this study conducted a bibliometric analysis of the publication on SC-EVs for DM from 2017 to 2021.…”
Section: Discussionmentioning
confidence: 99%
“…β cell uptake of EVs secreted by immune cells can induce β cell dysfunction and apoptosis. 55 Conversely, stem cell-derived EVs have immunomodulatory effects on multiple cells involved in the autoimmune response leading to T1DM, 56 and treatment with MSC-derived EVs has been reported to stimulate islet β cell regeneration and insulin production to control systemic glucose levels in a rat model of T1DM. 57 T2DM differs from T1DM as it is primarily caused by dysregulation of the insulin signaling pathway in response to proinflammatory responses that develop during excess weight gain from excess caloric intake.…”
Section: Ev Diagnostic Prognostic and Therapeutic Applicationsmentioning
confidence: 99%
“…In SSc, MSC-Exos can exert antifibrotic and anti-inflammatory effects by promoting M1 macrophage polarization and inhibiting M2 macrophage polarization (84). In T1D, MSC-Exos are able to increase the ratio of Treg in PBMCs of T1D patients and inhibit the proliferation of Th1 and Th17 cells in T1D mice (85). In addition, MSC-Exos have a positive effect on promoting the survival and generation of b cells (85).…”
Section: Msc-exosmentioning
confidence: 99%
“…In T1D, MSC-Exos are able to increase the ratio of Treg in PBMCs of T1D patients and inhibit the proliferation of Th1 and Th17 cells in T1D mice (85). In addition, MSC-Exos have a positive effect on promoting the survival and generation of b cells (85). Recent studies have shown that the content of protein in exosomes is much higher than that of miRNAs, so MSC-Exos are highly likely to treat AIDs mainly through proteins, which provides a new idea for the study of mechanism associated with MSC-Exos in the treatment of AIDs (7).…”
Section: Msc-exosmentioning
confidence: 99%